Digital Holography Digital Hologram Recording, Numerical Reconstruction, and Related Techniques - Schnars, Ulf; Jüptner, Werner (Springer Berlin Heidelberg : Imprint: Springer, 2005)
This book presents a self-contained treatment of the principles and major applications of digital hologram recording and numerical reconstruction (Digital Holography). The first part deals with optical foundations and the theory of holography. The next section describes how to record holograms directly with an electronic sensor (CCD) and describes the various reconstruction techniques. A special chapter is designated to digital holographic interferometry with applications in deformation and shape measurement and refractive index determination. Applications in imaging and microscopy are also described. The next part discusses special techniques such as digital light-in-flight holography, holographic endoscopy, information encrypting and comparative holography. In the last chapter related techniques of speckle metrology are treated briefly.